Marketing flexibility of tourism human resources and its impact on enhancing tourist behaviour - Azeez, Salam Jaaffar (Technium Business and Management, 2025)
The research shows the impact of human resource marketing flexibility in enhancing workers’ tourism behaviour in first-class hotels in the holy governorate of Karbala. The research began with a realistic problem, according to which several questions were identified, including clarifying the nature of the correlational and influential relationship between the research variables in the field. The research adopted the scale of (Camisom et al., 2010) (Beraha et al., 2018) in measuring marketing flexibility, which was measured in three dimensions: (flexibility of participation (part), flexibility of interaction (inte), flexibility of implementation (impl)), as for the tourist behaviour measure. The researcher adopted a scale of (Kotler et al., 2012) and (Durmaz et al., 2014), which was measured by four dimensions (Pirs, Lear, Perc, Moti). As for the central administration in collecting research data, the researcher relied on the questionnaire, and the sample was chosen from workers in first-class hotels in the Holy Governorate of Karbala, which numbered (141) workers and were distributed among (10) hotels registered in the Karbala Tourism Directorate, where (103) factors determined the sample size according to the Stephen Thompson equation. For processing and analysing the data statistically, structural equation modelling represented by (confirmatory factor analysis) was used, in addition to a set of descriptive statistical measures such as the Pearson correlation coefficient for ranks, and simple linear regression analysis using several statistical programs, including (Amos, V.24), (Spss, V.26). The results of the analysis proved the existence of a significant correlation and influence of the marketing flexibility of human resources in enhancing tourism behaviour among workers in hotel establishments, first-class hotels, the research sample, as the results indicated progress for the interaction flexibility dimension, which is dependent on the flexibility variable. Marketing, then the flexibility of the implementation dimension, and finally, the flexibility of the participation dimension have an impact in enhancing the tourist behaviour of hotel workers in the research sample. The order of the dimensions of the tourist behaviour variable came according to its importance (personality, perception, learning, and motivation).